Synthesis and Antimicrobial Evaluation of Some Novel Trisubstituted s-Triazine Derivatives Based on Isatinimino, Sulphonamido, and Azacarbazole - Sonika Jain; Anamika Sharma; Meenakshi Agrawal; Swapnil Sharma; Jaya Dwivedi; D. Kishore (Journal of Chemistry)
A study directed towards exploring the temperature-dependent reactivity of the chlorine atoms of 2,4,6-trichloro-s-triazine (TCT) in the nucleophilic displacement reaction, allowed a facile replacement of its chlorine atoms in succession with (i) N-amino methyl substituted isatin-3-hydrazones, (ii) N1-substituted-4-amino benzene sulphonamides, and (iii) 8-amino-4-oxo-N-benzyl-azacarbazole to produce the corresponding 2,4,6-trisubstituted-s-triazine, namely; 2-(N-amino methyl substituted isatin-3-hydrazinyl)-4-(N1-substituted-4′-amino benzenesulfonamidyl)-6-(8′-amino-4′-oxo-N-benzylazacarbazolyl)-1,3,5-triazine derivatives in acceptable yields. The compounds prepared were further evaluated for their antibacterial activity against E. coli and B. subtilis and antifungal activities against A. niger and A. flavus, and some of them showed promising activity profile.